2019
DOI: 10.1119/1.5084929
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Program Learning Outcomes: A Tale of Self-Discovery

Abstract: Learning assessment at two-year colleges is growing, but not much has been published about it yet. In general, our smaller classrooms, diverse student population, high proportion of adjunct faculty, and academic freedom in teaching methods and tools set the stage for a different approach to assessment than at four-year institutions. This is the story of how faculty at Suffolk County Community College (SCCC) are working through a long-term assessment plan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…The measurement model and structural model were validated using empirical data and met the criterion suggested by [17]. The study revealed a relationship between PEOs and PLOs, and the findings were in tandem with [10], [11], and [12]. The results indicated that the relationship of PEOs and PLOs was statistically significant.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The measurement model and structural model were validated using empirical data and met the criterion suggested by [17]. The study revealed a relationship between PEOs and PLOs, and the findings were in tandem with [10], [11], and [12]. The results indicated that the relationship of PEOs and PLOs was statistically significant.…”
Section: Discussionmentioning
confidence: 84%
“…In establishing the relationship between PLOs and PEOs in the form of SEM, the study examines the relevant literature on OBE, PEOs and PLOs. As stated by [10], [11], [12], the PLOs and PEOs are linked in the sense that the development of PLOs must take into consideration of PEOs and OBE. [13] revealed that Course Learning Outcomes (CLOs), PLOs and PEOs are an interrelated learning outcomes of curriculum design.…”
Section: Purpose Of the Studymentioning
confidence: 99%
“…, 2022a , b ). PLOs can be used to create and update curricular maps, design and implement assessment plans, and refine curriculum and co-curricular supports based on the results of assessment ( Towns, 2010 ; Johnson and Envick, 2014 ; Denicoló, 2019 ). In addition, PLOs communicate the main goals of a degree to current and prospective students of the program, as well as instructors, staff, parents, and other stakeholders involved in the degree program ( Praslova, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, we choose to use the term “program learning outcome” or “PLO” in our work to refer to any set of goals, objectives, or competencies that an undergraduate biology degree program lists for its degree. We choose this term because of its use in past literature ( Denicoló, 2019 ) and because the term “outcome” is the term most commonly referenced among the major accreditation bodies ( Table 5 ). Similarly, we incorporate a broad, inclusive definition of this term, given our goals of characterizing what undergraduate biology programs are listing and communicating to students and faculty about different programs’ intended aims.…”
Section: Introductionmentioning
confidence: 99%
“…Under the applicable curriculum standards, characteristics of skills are formulated into two types, namely general and specific skills. Assessment of the achievement of PLO is essential; unfortunately, there are not many publications on this subject [4].…”
Section: Introductionmentioning
confidence: 99%